Managerial Risk, Innovation, and Organizational Decline - Latham, Scott F.; Braun, Michael (Journal of Management, 2009)
This article introduces managers' personal risk considerations into the relationship between organizational decline and innovation. The agency-based perspective is used to complement threat rigidity theory and prospect theory in examining how managerial ownership and slack resources affect managers' innovation decisions when firms experience poor performance. The findings indicate that more managerial ownership decelerates innovation spending. The availability of slack resources also reduces the rate of innovation investments. Firms with more slack resources and higher levels of managerial ownership jointly reduce innovation under circumstances of decline. Last, poorly performing firms that continue investments in innovation exhibit a lower probability of survival.